Friction Stir Welding of Dissimilar Aluminium Alloys for Marine Applications. - NOR ASYIKIN BINTI MOHD YUSOF; DR. SHAZAREL BIN SHAMSUDIN (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The FSW process utilises the aluminium alloys of AA6061-T6 and AA5083-H116 as workpieces. The size of the specimen is 65mm x 50mm x4mm and butt joint type is selected. The FSW parameters selected are material thickness (3 mm, 4 mm, and 5 mm), rotational speed (800 rpm, 1200 rpm, and 1600 rpm), feed rate/linear speed (30 mm/min, 60 mm/min, and 90 mm/min), pin length (92.5 %, 95% and 97.5% of material thickness) and dwell time (15 min, 20 min and 25 min). The optimization of the responses of tensile strength and hardness will be carried out through Response Surface Methodology (RSM) design. The tensile test is carried out using Universal Testing Machine. The microhardness underneath the sub-surface layer of the weld joint is measured by Vickers Hardness Tester. Linear speed and pressure required welding and types of tools. Samples friction stir welding were added depending on the application of design of experiment (DOE) method by means of (RSM) and use Minitab to get optimization of the tensile strength and linear relationship between the results and parameters.